2012
DOI: 10.1371/journal.pone.0032875
|View full text |Cite
|
Sign up to set email alerts
|

Skin Regeneration in Adult Axolotls: A Blueprint for Scar-Free Healing in Vertebrates

Abstract: While considerable progress has been made towards understanding the complex processes and pathways that regulate human wound healing, regenerative medicine has been unable to develop therapies that coax the natural wound environment to heal scar-free. The inability to induce perfect skin regeneration stems partly from our limited understanding of how scar-free healing occurs in a natural setting. Here we have investigated the wound repair process in adult axolotls and demonstrate that they are capable of perfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
259
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(279 citation statements)
references
References 73 publications
20
259
0
Order By: Relevance
“…More recent studies in the axolotl reported the recruitment of neutrophils in deep tissue wounds but not in regenerating limbs (8,31). By contrast, using a range of methods, the present study confirms the active involvement of macrophages within the regenerating axolotl limb.…”
Section: Pbs-liposupporting
confidence: 73%
See 1 more Smart Citation
“…More recent studies in the axolotl reported the recruitment of neutrophils in deep tissue wounds but not in regenerating limbs (8,31). By contrast, using a range of methods, the present study confirms the active involvement of macrophages within the regenerating axolotl limb.…”
Section: Pbs-liposupporting
confidence: 73%
“…S9). α-Smooth muscle actin (α-SMA) is an established marker for differentiated myofibroblasts displaying subepithelial localization (31)(32)(33) in several species. Macrophage-depleted animals showed increased numbers of α-SMA-positive cells compared with the normally low levels observed in control animals at 20 dpa (Fig.…”
Section: Mononuclear Phagocytes Regulate Regenerative Gene Expressionmentioning
confidence: 99%
“…After three weeks, it became thicker and was arranged in different directions in a network like manner that mimic control skin. These findings might be attributed to the initial deposition of thin collagen fibrils (type III) that were later resorbed and replaced with thicker fibrils (type I) aligned with stress lines indicating maturity of wound (22,25,26). Eventually, in delayed healing of wounds in systemically treated group after three weeks, collagen fibres were still relatively thin and oriented parallel to the skin indicating delayed healing.…”
Section: Fig 12mentioning
confidence: 97%
“…This might facilitate earlier progress to the next phases of wound healing as reduced inflammation promotes regeneration rather than scarring (22). This notion might explain wound regeneration in BMSCs-treated groups and scar formation in non treated group.…”
Section: Modeling and Apoptosis (16)mentioning
confidence: 97%
See 1 more Smart Citation